Spatial proximity, enterprise agglomeration, and innovation output: Mechanisms and insights from China - Mao Zhang; Fei Qin (Sustainable Futures)
As global economic transformation accelerates, enterprise agglomeration is pivotal in driving regional innovation and economic growth, particularly in late-developing economies with limited resources. This study introduces a dynamic geospatial measurement method using enterprises’ latitude and longitude data to quantify agglomeration levels, overcoming the limitations of static indicators. Using data from A-share listed companies in Shanghai and Shenzhen (2012–2022), the findings show that enterprise agglomeration significantly enhances innovation quantity and quality, especially in high-tech manufacturing industries with extensive cycles, scale, and reputations, yet may significantly inhibit innovation via intensified competition. Key mechanisms include local knowledge networks, inter-enterprise reciprocity, and government subsidies. Moreover, the agglomeration effect diminishes with greater geographical distance, highlighting spatial dependence. This paper advances agglomeration economy theory while offering actionable policy insights for resource-constrained countries to foster innovation-driven, sustainable development.